Association of ECG early repolarization phenomena and “T-infantile” with autonomic regulation of the heart rhythm in young athletes - Mykhaliuk, Ye. L.; Syvolap, V. V.; Hunina, L. M.; Potapenko, M. S.; Kaddah, D. Al; Михалюк, Євген Леонідович; Сиволап, Віталій Вікторович; Гуніна, Л. М.; Потапенко, Марина Станіславівна; Каддах, Діана Аль; Михалюк, Е. Л.; Сыволап, В. В.; et al. (Запорізький державний медичний університет, 2020)
The incidence of autonomic disorders in athletes varies widely from 6.2 % to 36.5 %. With the improving sport qualification, the frequency and severity of autonomic dysfunction increase. Various ECG phenomena, including SEVR and “T-infantile” are associated with a type of autonomic tone. Moreover, ANS dysfunction does not determine the genesis, but only contributes to the manifestation of these syndromes signs. The association between the ECG phenomena and autonomic dysfunction nature, age and gender of athletes remains an open question. The purpose of this work was to study the incidence of juvenile T-wave and SEVR, their association with the autonomic regulation of heart rate in young athletes in the age range between 6 and 17 years. Materials and methods. An electrocardiographic study and 5-minute recordings of the heart rate variability were carried out in 3720 children and adolescents aged between 6 and 17 years, of them 74.6 % were boys (n = 2774) and 25.4 % were girls (n = 946), engaged in various sports. The study results. The “T-infantile” phenomenon was detected in 1.5 % (56/3720) of athletes, among them 1.07 % (40) were boys and 0.43 % (16) were girls. In five (12.5 %) athletes, “T-infantile” was combined with incomplete right bundle branch block, in 3 (7.5 %) – with short PQ syndrome, and in one (2.5 %) – with SEVR. In addition to the ECG signs of “T-infantile”, three (18.75 %) athletes additionally had incomplete RBBB, and also short PQ syndrome was detected in one athlete (6.25 %). A comparative analysis of HRV indices in boys and girls with the “T-infantile” phenomenon showed that in boys, the D value was significantly higher, reflecting the vagal regulation activity of the heart rhythm (0.403 ± 0.028 s versus 0.311 ± 0.025 s, P = 0.019). When assessing the autonomic state according to R. M. Baevsky, it was found that 40 % (n = 16) of male athletes with T-infantile ECG phenomenon had an increased parasympathetic nervous system tone, 50 % (n = 20) had normal ANS tone, and 10 % (n = 4) had an increased sympathetic nervous system tone. In girls, there were 31.25 % (n = 5) with increased PNS tone, 50 % (n = 8) with normal ANS tone and 18.75 % (n = 3) with increased SNS tone, respectively. Conclusions. Early repolarization syndrome and “T-infantile” are more common in case of increased parasympathetic nervous system tone rather than in other variants of autonomic tone. A combination of parasympathetic overactivity with these ECG phenomena is observed mainly in males. The phenomenon of “T-infantile” can be combined with incomplete right bundle branch block in young athletes of both sexes.

Частота встречаемости вегетативных расстройств у спортсменов колеблется в широком диапазоне – от 6,2 % до 36,5 %. С ростом спортивной квалификации частота и тяжесть вегетативной дисфункции увеличиваются. Различные ЭКГ-фено¬мены, в том числе СРРЖ и «Т-infantile» имеют сопряженность с типом вегетативного тонуса. При этом дисфункция АНС не определяет генез, а только способствует проявлению признаков этих синдромов. Открытыми остаются вопросы связи ЭКГ-феноменов с характером вегетативной дисфункции, возрастом и полом спортсменов. Цель работы – изучить частоту встречаемости ювенильного зубца Т и СРРЖ, их ассоциации с вегетативной регуляцией сердечного ритма у юных спортсменов в возрастном диапазоне от 6 до 17 лет. Материалы и методы. Проведено электрокардиографическое исследование и запись 5-минутных интервалов вариабельности сердечного ритма у 3720 детей и подростков в возрасте от 6 до 17 лет, мальчиков – 74,6 % (n = 2774), девочек – 25,4 % (n = 946), занимающихся различными видами спорта. Результаты. Феномен «T-infantile» обнаружен у 1,5 % (56/3720) спортсменов, из них 1,07 % (n = 40) мальчиков и 0,43 % (n = 16) девочек. У 5 (12,5 %) спортсменов «Т-infantile» сочетался с неполной блокадой правой ножки пучка Гиса, у 3 (7,5 %) – с синдромом укороченного PQ, у 1 (2,5 %) – с синдромом ранней реполяризации желудочков. Кроме ЭКГ признаков «Т-infantile» у 3 (18,75 %) спортсменок дополнительно зафиксирована неполная блокада ПНПГ, а у одной спортсменки (6,25 %) обнаружен синдром укороченного PQ. Сравнительный анализ показателей ВСР у мальчиков и девочек с феноменом «Т-infantile» показал, что у мальчиков достоверно больше величина Д, отражающая активность вагусной регуляции ритма сердца (0,403 ± 0,028 с против 0,311 ± 0,025 с, р = 0,019). При оценке вегетативного состояния по Р. М. Баевскому у спортсменов с ЭКГ-феноменом «Т-infantile» установлено, что у 40 % (n = 16) мальчиков имела место ваготония, у 50 % (n = 20) – эйтония, у 10 % (n = 4) – симпатикотония. Среди девочек было 31,25 % (n = 5) ваготоников, 50 % (n = 8) эйтоников, 18,75 % (n = 3) симпатикотоников. Выводы. Синдром ранней реполяризации желудочков и «Т-infantile» отмечают при ваготонии сравнительно чаще, чем при других вариантах вегетативного тонуса. Сопряжение избыточных парасимпатических влияний с этими ЭКГ-феноменами обнаруживают преимущественно у лиц мужского пола. Феномен «Т-infantile» может сочетаться у юных спортсменов с неполной блокадой правой ножки пучка Гиса.

Частота вегетативних розладів у спортсменів коливається в широкому діапазоні – від 6,2 % до 36,5 %. З підвищенням спортивної кваліфікації частота й тяжкість вегетативної дисфункції збільшуються. Різні ЕКГ-феномени, зокрема СРРШ і «Т-infantile», мають зв’язок із типом вегетативного тонусу. Дисфункція АНС не визначає ґенез, а тільки зумовлює прояву ознак цих синдромів. Відкритими залишаються питання зв’язку ЕКГ-феноменів із характером вегетативної дисфункції, віком і статтю спортсменів. Мета роботи – вивчити частоту виявлення ювенільного зубця Т і СРРШ, їхньої асоціації з вегетативною регуляцією серцевого ритму в юних спортсменів у віковому діапазоні від 6 до 17 років. Матеріали та методи. Здійснили електрокардіографічне дослідження та запис 5-хвилинних інтервалів варіабельності серцевого ритму у 3720 дітей і підлітків віком від 6 до 17 років, хлопців – 74,6 % (n = 2774), дівчат – 25,4 % (n = 946), які займаються різними видами спорту. Результати. Феномен «T-infantile» виявили у 1,5 % (56/3720) спортсменів, з-поміж них 1,07 % (n = 40) хлопців і 0,43 % (n = 16) дівчат. У 5 (12,5 %) спортсменів «Т-infantile» поєднувався з неповною блокадою правої ніжки пучка Гіса, у 3 (7,5 %) – із синдромом укороченого PQ, у 1 (2,5 %) – з синдромом ранньої реполяризації шлуночків. Крім ЕКГ-ознак «Т-infantile» у 3 (18,75 %) спортсменок додатково зафіксована неповна блокада ПНПГ, в 1 (6,25 %) спортсменки зафіксували синдром укороченого PQ. Протягом порівняльного аналізу показників ВСР у хлопців і дівчат із феноменом «Т-infantile» з’ясували: у хлопців вірогідно більша величина Д, що показує активність вагусної регуляції ритму серця (0,403 ± 0,028 с проти 0,311 ± 0,025 с, р = 0,019). Оцінюючи вегетативний стан за Р. М. Баєвським у спортсменів з ЕКГ-феноменом «Т-infantile», встановили: у 40 % (n = 16) хлопців була ваготонія, у 50 % (n = 20) – ейтонія, в 10 % (n = 4) – симпатикотонія. З-поміж дівчат 31,25 % (n = 5) ваготоників, 50 % (n = 8) ейтоників і 18,75 % (n = 3) симпатикотоників. Висновки. Синдром ранньої реполяризації шлуночків і «Т-infantile» виявляють у випадку ваготонії порівняно частіше, ніж при інших варіантах вегетативного тонусу. Поєднання надлишкових парасимпатичних впливів із цими ЕКГ-фено¬менами спостерігають здебільшого в осіб чоловічої статі. Феномен «Т-infantile» може поєднуватися в юних спортсменів із неповною блокадою правої ніжки пучка Гіса.
Асоціація ЕКГ-феноменів ранньої реполяризації і «Т-infantile» з вегетативною регуляцією серцевого ритму в юних спортсменів
Ассоциация ЭКГ-феноменов ранней реполяризации и «Т-infantile» с вегетативной регуляцией сердечного ритма у юных спортсменов
Михалюк Є. Л. - ORCID ID: 0000-0003-3607-7619; Сиволап В. В. - ORCID ID: 0000-0001-9865-4325.
Keywords: “Т-infantile”; young athletes; autonomic balance; юні спортсмени; вегетативний баланс; юные спортсмены; вегетативный баланс